WIPI2 enhances the vulnerability of colorectal cancer cells to erastin via bioinformatics analysis and experimental verification - Yu, Liying; Luo, Yan; Ding, Xile; Tang, Miaomiao; Gao, Huan; Zhang, Renfang; Chen, Mingfu; Liu, Yuchen; Chen, Qiongxia; Ouyang, Yanli; Wang, Xiang; Zhen, Hongyan (Frontiers in Oncology, 2023)
WD Repeat Domain Phosphoinositide Interacting 2 (WIPI2) is a WD repeat protein that interacts with phosphatidylinositol and regulates multiprotein complexes by providing a β-propeller platform for synchronous and reversible protein-protein interactions assembled proteins. Our study is to focus on investigating the effect of WIPI2 on the growth and ferroptosis of colorectal cancer (CRC) cells and its potential mechanism. Public data from the TCGA platform shows that WIPI2 expression is significantly elevated in colorectal cancer tissues compared to paracancerous tissues, and high WIPI2 expression predicts poor prognosis for CRC patients. To further investigate the mechanism of WIPI2 action in CRC, we constructed the siRNAs targeting the WIPI2 sequence si-WIPI2 and found that the knockdown of WIPI2 expression could inhibit the growth and proliferation of HCT116 and HT29 cells. Ferroptosis, a novel iron-dependent form of cell death, it is usually accompanied with the accumulation of membrane lipid peroxides. We found that the expression level of ACSL4 decreased and that of GPX4 increased when WIPI2 was knocked down, suggesting that WIPI2 can potentially positively regulate CRC ferroptosis. Meanwhile, both NC and si groups were able to further inhibit cell growth activity, as well as increase WIPI2 and decrease GPX4 expression when treated with Erastin, but the rate of cell viability inhibition and the trend of protein changes were more significantly in the NC group than si group, which indicated that Erastin induced CRC ferroptosis through the WIPI2/GPX4 pathway thereby enhancing the sensitivity of colorectal cancer cells to Erastin. In conclusion, our study suggests that WIPI2 has a promotional effect on the growth of colorectal cancer cells, and it also plays an important role in the ferroptosis pathway.